Analisis Idiosinkratik 10 Tahun Kebijakan Luar Negeri Jokowi : Studi Kasus Peran Indonesia Terkait Pengungsi Rohingya - Devi, Nila Aditya; Khoiriyah, Ummu Masyithotul (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
The policies of a country are determined by a leader and the background of a leader shapes his political personality. The idiosyncratic of a State leader can be influenced by the populism of his country. Indonesia is a democratic country where there is a change of leadership and changes in domestic and foreign policies. Jokowi during his tenure as President of Indonesia has a foreign policy direction that prioritizes diplomacy and negotiations. Jokowi's idiosyncratic in shaping foreign policy related to Rohingya refugees can be seen in the efforts of diplomacy and humanitarian assistance for Rohingya refugees. The embodiment of Indonesia's free-active foreign policy is manifested in policies for domestic pro-people and for international participation in cooperation and the realization of regional and global peace.